Answer:
x = -2 and x = -3
Explanation:
It is required to find the roots of the equation. The general quadratic equation is :
The solution of above equation is:
![x=(-b\pm √(b^2-4ac) )/(2a)](https://img.qammunity.org/2021/formulas/mathematics/college/fbgkl84j2w1o80jqir10jtm69c0hwwzljf.png)
The given equation is :
![x^2+5x+6=0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4nglefrkbg1jydmh55ubg92qxscv9lhu7r.png)
Its solutions are :
![x=(-b+ √(b^2-4ac) )/(2a),(-b- √(b^2-4ac) )/(2a)](https://img.qammunity.org/2021/formulas/mathematics/college/g2j9pszo0on4whvrnz0hgg4zkguqvw4wio.png)
Here, a = 1, b = 5 and c = 6
![x=(-5+ √((5)^2-4* 1* 6) )/(2* 1),(-5- √((5)^2-4* 1* 6) )/(2* 1)\\\\x=-2,-3](https://img.qammunity.org/2021/formulas/mathematics/college/j29pijzoka5vzfg9zr0ac509m75azea9ic.png)
So, the values of x are -2 and -3. Hence, the correct option is (d).